Water User Associations (WUAs) in Kyrgyzstan : a case study on institutional reform in local irrigation management - Sehring, Jenniver; Justus Liebig University Giessen (My University, 2005)
The present study was compiled within the framework of the research project "Water shortage, water use conflicts and water management in arid environments of Central Asia". Its objective is to analyze the causes and the effects of the growing water shortage and the increasing deterioration of the water quality in this area. The research activities compare the situation in four inland basins of Central Asia: the Aral Sea Basin, the Ili-Balkhash Basin, the Issyk-Kul Basin, and the Tarim Basin. One component of the project focuses on questions of water management on interstate as well as national level. This paper concentrates on the local level, where political decisions concerning water management have to be implemented and where problems of access to and availability of water have the most direct consequences.
Keywords: ddc:630